Innovative and agile contracting for digital transformation and industry 4.0 - Shalan, Mohammad Ali, 1972-; Algarni, Mohammed Ayedh, 1975- (Advances in business information systems and analytics (ABISA) book series., 2021)
"This book introduces innovative contracting to fit the era of digital transformation and industry 4.0 by addressing the motivations to promote such a new style of contracting and listing the shortcomings of traditional contracting"--